Experimental comparison between low salt rejection and counter flow reverse osmosis for produced water desalination - Joel Minier-Matar (17052378) (2025)
Low salt rejection reverse osmosis (LSRRO) and counterflow reverse osmosis (CFRO) are gaining momentum for the treatment of highly saline brines, each process with its own trade-offs. In this study, the performance of the two systems was experimentally evaluated on three different stages using sodium chloride solutions (100 g/L salinity) and on real industrial wastewater (120 g/L salinity) from oil and gas operations. Results showed that both systems can treat saline water, producing high-quality permeate. Based on experimental data and model predictions, a system design was developed, and results showed that CFRO requires 3 stages while LSRRO requires 4 stages to achieve the same RO permeate quality. The specific energy consumption for LSRRO and CFRO were 18.1 and 7.1 kWh/m3 permeate, respectively. CFRO required 5 times more membrane area compared to LSRRO due to the lower water fluxes, which translated to higher capital investment and larger footprint. CFRO was projected to have lower greenhouse gas emissions compared to LSRRO (3.0 vs 7.6 kg CO2/m3p), but it generates more solid waste and requires more cleaning chemicals. While both technologies are feasible for desalination of high-salinity streams, there are several possible areas for improvements. As more experimental data are generated from these emerging technologies, their operating performance can be further optimized for field applications. Other Information Published in: Desalination License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.desal.2025.119305